Spin–exciton interaction and related micro-photoluminescence spectra of ZnSe:Mn DMS nanoribbon. (1st February 2017) - Hou, Lipeng; Zhou, Weichang; Zou, Bingsuo; Zhang, Yu; Han, Junbo; Yang, Xinxin; Gong, Zhihong; Li, Jingbo; Xie, Sishen; Shi, Li-Jie
Abstract: For their spintronic applications the magnetic and optical properties of diluted magnetic semiconductors (DMS) have been studied widely. However, the exact relationships between the magnetic interactions and optical emission behaviors in DMS are not well understood yet due to their complicated microstructural and compositional characters from different growth and preparation techniques. Manganese (Mn) doped ZnSe nanoribbons with high quality were obtained by using the chemical vapor deposition (CVD) method. Successful Mn ion doping in a single ZnSe nanoribbon was identified by elemental energy-dispersive x-ray spectroscopy mapping and micro-photoluminescence (PL) mapping of intrinsic d – d optical transition at 580 nm, i.e. the transition of 4 T 1 ( 4 G ) →  6 A 1 ( 6 s ), . Besides the d – d transition PL peak at 580 nm, two other PL peaks related to Mn ion aggregates in the ZnSe lattice were detected at 664 nm and 530 nm, which were assigned to the d – d transitions from the Mn 2+ –Mn 2+ pairs with ferromagnetic (FM) coupling and antiferromagnetic (AFM) coupling, respectively. Moreover, AFM pair formation goes along with strong coupling with acoustic phonon or structural defects. These arguments were supported by temperature-dependent PL spectra, power-dependent PL lifetimes, and first-principle calculations. Due to the ferromagnetic pair existence, an exciton magnetic polaron (EMP) is formed and emits at 460 nm. Defect existence favors the AFM pair, which also can account for its giant enhancement of spin–orbital coupling and the spin Hall effect observed in PRL97, 126603(2006) and PRL96, 196404(2006). These emission results of DMS reflect their relation to local sp-d hybridization, spin–spin magnetic coupling, exciton–spin or phonon interactions covering structural relaxations. This kind of material can be used to study the exciton–spin interaction and may find applications in spin-related photonic devices besides spintronics.